2019
DOI: 10.5861/ijrse.2019.4004
|View full text |Cite
|
Sign up to set email alerts
|

The effect of interpersonal communication and self-adjustment to the work readiness of vocational high school students

Abstract: Interpersonal communication and self-adaptation are two factors that can influence the work readiness of students. This study aims to find out the effect of interpersonal communication and self-adaptation to students' work readiness. The subjects in this study were students of class XII of SMK Negeri 1 Seyegan totaling 174 students. The sampling technique is cluster random sampling. Methods of data collection in this study are work readiness scale, interpersonal communication scale, and self-adaptation scale. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…Recognizing factors that facilitate or hinder work readiness can inform educators and hospital administrators of the essential components for formulating effective strategies to support new graduate nurses. Several studies have reported determinants of work readiness among graduate nurses, including emotional intelligence, psychological capital (Masole & van Dyk, 2016), interpersonal communication, self-adjustment (Tentama et al, 2019), students' perceptions of the clinical education environment (Dudley et al, 2020), interpersonal relationships, leadership experience, award of academic scholarship, prior work experience, willingness to be a nurse (Li et al, 2020), child-care experience, length of the nurse residency programme (Hayter, 2017), professional passion, clinical confidence, class size, the applicability of school education in work and perceived quality of education and practice training (Ergun & Beyhan, 2017). However, previous studies separately focused on personal, educational or clinical factors, without considering such factors simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Recognizing factors that facilitate or hinder work readiness can inform educators and hospital administrators of the essential components for formulating effective strategies to support new graduate nurses. Several studies have reported determinants of work readiness among graduate nurses, including emotional intelligence, psychological capital (Masole & van Dyk, 2016), interpersonal communication, self-adjustment (Tentama et al, 2019), students' perceptions of the clinical education environment (Dudley et al, 2020), interpersonal relationships, leadership experience, award of academic scholarship, prior work experience, willingness to be a nurse (Li et al, 2020), child-care experience, length of the nurse residency programme (Hayter, 2017), professional passion, clinical confidence, class size, the applicability of school education in work and perceived quality of education and practice training (Ergun & Beyhan, 2017). However, previous studies separately focused on personal, educational or clinical factors, without considering such factors simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Second, teamwork is necessary for building interpersonal skills as it is a part of the effort to foster an attitude of collaboration between one another. Teamwork can provide a broad visionary view of common goals [26]. A good team also positively shapes the personalities of its members.…”
Section: Relation Between Constructive Knowledge Workmentioning
confidence: 99%
“…In addition, the resulting effect on this variable has a coefficient value of 0.197; if students' interpersonal skills are high, their work readiness is also higher for the resulting coefficient of influence. Interpersonal skills, which include skills in the form of social sensitivity, relationship building, working with others, listening, and communication, affect work readiness [12,26,36]. Sulistyobudi and Kadiyono [25] added that, in addition to interpersonal skills, vocational schools aim to equip vocational school students with sufficient knowledge, skills, and attitudes before they enter the industrial world.…”
Section: Interpersonal Skills Affect Work Readinessmentioning
confidence: 99%
“…Siswa yang mengembangkan keterampilan komunikasi interpersonal yang baik juga tampil lebih baik dalam akademik, dan manfaatnya terus berlanjut setelah mereka menyelesaikan pendidikannya (Callihan et al, 2012). Hasil penelitian ini juga sejalan dengan kajian penelitian terdahulu oleh Tentama et al (2019) dengan hasil penelitian menunjukan pengaruh yang signifikan antara komunikasi interpersonal dan kesiapan kerja siswa kelas XII SMK Negeri Seyegan, dan penelitian oleh Fathimah (2022) yang juga menyatakan bahwa keterampilan komunikasi interpersonal memiliki pengaruh yang positif dan signifikan terhadap kesiapan kerja siswa kelas XII SMKN 2 Magelang.…”
Section: Uji Hipotesisunclassified